2009
DOI: 10.1177/030089160909500424
|View full text |Cite
|
Sign up to set email alerts
|

Perianal Granular Cell Tumor: Report of a Case and Review of the Literature

Abstract: Granular cell tumors are rarely observed in the perianal region. Their existence must always be borne in mind in the differential diagnosis of perianal neoplasms. In most cases surgical excision is curative, but potential malignant transformation must be considered during therapeutic procedures and follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 16 publications
(18 reference statements)
0
19
0
Order By: Relevance
“…Other sites include the skin, gastrointestinal tract, breast, biliary tract, respiratory tract, genital tract, orbit and mastoid. About 8% of GCT lesions are localized to the gastrointestinal tract and the esophagus accounts for the majority of these cases followed by the large intestine [3, 4]. There are less than 30 cases of perianal GCT reported in the literature, as of 2015, making it a rare anal neoplasm [2, 3, 5].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Other sites include the skin, gastrointestinal tract, breast, biliary tract, respiratory tract, genital tract, orbit and mastoid. About 8% of GCT lesions are localized to the gastrointestinal tract and the esophagus accounts for the majority of these cases followed by the large intestine [3, 4]. There are less than 30 cases of perianal GCT reported in the literature, as of 2015, making it a rare anal neoplasm [2, 3, 5].…”
Section: Introductionmentioning
confidence: 99%
“…About 8% of GCT lesions are localized to the gastrointestinal tract and the esophagus accounts for the majority of these cases followed by the large intestine [3, 4]. There are less than 30 cases of perianal GCT reported in the literature, as of 2015, making it a rare anal neoplasm [2, 3, 5]. Most of the reported cases are single case reports; however, the US Armed Forces Institute of Pathology, Johnston et al , reported 75 cases of gastrointestinal GCT, of which 16 cases were localized to the perianal region [2].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations